The Correlation Between Consuming Fast Food And Obesity Of Primary School-Aged Children In SD Al-Azhar Medan - Qori An-Nabil, Muhammad; Machrina, Yetty (CV RIFAINSTITUT, 2022)
Fast food is high calorie foods and is preferred by children, especially in the primary level. Extensive consumption of fast food can lead to obesity. In Indonesia the prevalence of obesity in primary school-aged children increases from 5.0 % to 16.0% this increase is due to the habit of consuming fast food. To determine the correlation of fastfood consumption with obesity on primary school-aged children. This research is analytic applying case control study design. The data of weight and height are collected by anthropometric measurements using Body Mass Index (BMI), within distributing questionnaires for nutritional status and physical activity while the fastfood consumption will be held by Food Frequency Questionnaires (FFQ) method. Hypotheses were analyzed by Chi-Square test results. The Chi-Square test results showed that there was a correlation between the frequency of fast food and the incidents of obesity (0.05). The result of the Chi-Square test showed that there was a correlation between the portion of fast food and the incident of obesity (0.05). There is a frequency correlation often consume fast food to the incident of obesity p value 0.01. There is correlation between large portions of fast food consumption to the incident of obesity with p value 0.001